Training on Coconut Jam in Moiso Village, South Jailolo District, West Halmahera Regency, North Maluku - Muhamad Saleh, Erna Rusliana; Rahakbauw, Siti Nurhalisa; Umabaihi, Juliyanti; Mutiara Mofu, Priscilla Agustina (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Moiso village is one of the villages in West Halmahera district, North Maluku which has coconut potential. Diversification of coconut products in this village is limited to processing copra products, so the results obtained are less than optimal. Especially when the price of copra drops. Therefore, an alternative diversification of coconut products is needed that can provide added value for the people in Moiso Village. Among others, processed into coconut jam. To support this, the community needs to be taught about the processing technology in accordance with Good Manufacturing Product (GMP) standards. The purpose of this activity is to transfer technology about coconut jam processing technology in accordance with Good Manufacturing Product Standards to the people of Moiso Village, especially PKK women by providing training. The training was given to 10 women from PKK and KWT in Moiso. The results of the training showed that 90% of PKK mothers did not know how to make it, but after being given training, 100% of them knew how to make coconut jam. This training opened the participants' insight that making coconut jam is easy. This can be seen from the test results given. At first before the training, 80% of the participants thought that making coconut jam was difficult. After the training, only 30% thought that making jam was difficult. In general, 90% of the participants were satisfied with this training.